Whole Body Vibration at Different Exposure Frequencies: Infrared Thermography and Physiological Effects. (14th January 2015) - Sonza, Anelise; Robinson, Caroline C.; Achaval, Matilde; Zaro, Milton A.
Abstract : The aim of this study was to investigate the effects of whole body vibration (WBV) on physiological parameters, cutaneous temperature, tactile sensitivity, and balance. Twenty-four healthy adults (25.3 ± 2.6 years) participated in four WBV sessions. They spent 15 minutes on a vibration platform in the vertical mode at four different frequencies (31, 35, 40, and 44 Hz) with 1 mm of amplitude. All variables were measured before and after WBV exposure. Pressure sensation in five anatomical regions and both feet was determined using Von Frey monofilaments. Postural sway was measured using a force plate. Cutaneous temperature was obtained with an infrared camera. WBV influences the discharge of the skin touch-pressure receptors, decreasing sensitivity at all measured frequencies and foot regions (P ≤ 0.05 ). Regarding balance, no differences were found after 20 minutes of WBV at frequencies of 31 and 35 Hz. At 40 and 44 Hz, participants showed higher anterior-posterior center of pressure (COP) velocity and length. The cutaneous temperature of the lower limbs decreased during and 10 minutes after WBV. WBV decreases touch-pressure sensitivity at all measured frequencies 10 min after exposure. This may be related to the impaired balance at higher frequencies since these variables have a role in maintaining postural stability. Vasoconstriction might explain the decreased lower limb temperature.